HUBUNGAN PENEMPATAN KARYAWAN TERHADAP PRESTASI KERJA PADA PT SANDHY PUTRA MAKMUR CABANG JAKARTA - Boma Jonaldy Tanjung; Ahmad Jaenuddin (Lembaga Pengembangan Kinerja Dosen, 2022)
Placement is not a simple matter because the wrong placement will be felt as a result not only on the work unit concerned but also on other units, so that the company's operations will be disrupted not only now but in the future. In the placement of employees should pay attention to the academic achievements of employees so that these employees can complete tasks and work and carry out the authority and responsibilities given by the company. On this basis, the author took the title